Keragaman genotipik entok (Cairina moschata) berdasarkan polimorfisme protein darah - Sutopo Sutopo; Dela Ayu Lestari; Asep Setiaji; Edy Kurnianto (Livestock and Animal Research, 2021)
Objective: The aim of this study was to identified genetic diversity of muscovy duck in Central Java through blood protein polymorphisms by using electrophoresis method.Methods: Blood sample was collected from a total of 60 muscovy ducks from the districts of Demak, Magelang and Pekalongan, 20 samples each. The Electrophoresis Polyacrylamide Gel of Electrophoresis–Thin Layer Electrophoresis (PAGE-TLE) was used in this study. Parameters observed were protein of albumin (Alb), ceruloplasmin (Cp), transferrin (Tf) and amylase-I (Am-I). Gene frequency, heterozygosity (Ho) and genetic distance were analyzed by using DISPAN program.Results: The results showed that the Alb, Cp, Tf and Am-I of muscovy duck showing polymorphic characters. Gene frequency of AlbB (0.61) was higher compared to AlbA (0.39). Gene frequency of CpA (0.62) was higher than the CpB (0.38). Furthermore, gene frequency of TfA and TfB were 0.32 and 0.68, respectively as well as gene frequency of Am-IA (0.82) was higher than Am-IB (0.18). Muscovy duck population of Demak showed higher Ho value for Alb and Am-I, whereas Magelang showed higher value for Cp and Tf. Population of muscovy duck of Demak showed closer genetic distance to Pekalongan than Magelang.Conclusions: The protein blood locus of three population of muscovy duck in Central Jawa showed polymorphic characters.